Properties of lime based thermal mortars - Lucas, Sandra S. (2011)
[Excerpt] Nowadays, major part of residential buildings electricity consumption is used for space heating and cooling, varying greatly during day and night and leading to differentiate tariffs. The shift, to off-peak periods, of this consumption presents a clear economical advantage and it can be achieved through energy thermal storage. Latent heat thermal energy storage, through the incorporation of PCM, presents the following advantages: narrow the gap between the peak and off-peak loads, levelling the electricity demand, decreasing the load on the network and eventual supply failure; reduce operation costs by shifting the electrical consumption from peak periods to off-peak periods; contribute to the interior thermal comfort in buildings, by using and storing solar energy (for space heating in winter) and storing natural cooling by ventilation at night during the summer, thus reducing electricity use for heating and cooling [1,2].The benefits to the comfort inside buildings appear during the change of the PCM. The transferences of energy that occur during the transitions solid-liquid and liquid-solid are generally the most used to help the acclimatization of the building. For that reason the PCM must be microencapsulated. The exterior of the microcapsules is made with a polymer [1,2].